Development of bacteria-based microcapsules for self-healing concrete - Xiao, Xi (Nanyang Technological University, 2023)
Over the past 15 years, bacteria-based self-healing concrete is developed to eliminate the costly and labor-intensive manual repair methods for the concrete cracks. Conventional bacteria immobilization/encapsulation techniques used in self-healing concrete usually lead to significant strength loss to the matrix because of the low strength and/or incompatibility of the protective materials with the matrix. And the encapsulation of concentrated bacteria spores in a single capsule can lead to uneven dispersion of bacteria in the matrix. Accordingly, the main objectives of the present study are to: (1) develop bacteria-based capsules for self-healing concrete which are compatible with matrix and could maintain the strength of the matrix while engaging self-healing, and (2) develop single bacteria spore encapsulation technology for self-healing concrete to realize the better dispersion of bacteria in the matrix thus leads to more stable and robust healing performance. The first objective is realized by using reactive magnesia cement (RMC) to encapsulate bacteria, where bacteria are encapsulated in RMC-based capsules alone or with nutrients, resulting in two types of capsules, namely RMC-B and RMC-BN capsules. Results show that the RMC-based bacterial capsules are functionally graded, highly compatible with the matrix, and able to engage self-healing while maintaining the strength of the matrix. Afterwards, further studies are carried out on single spore encapsulation technology in accordance with the second objective. Results show that layer-by-layer assembly can successfully encapsule single bacteria spore, and the resulted capsules can engage stable and robust healing due to the better dispersion of bacteria. Overall, this study presents novel self-healing techniques that are possible to be applied to real world owing to its superior self-healing performance and its compatibility with PC-based mixes.